Development of Realistic Mathematics Education (RME) Based Student Worksheets to Facilitate Junior High School Students' Mathematical Reasoning Ability - Tiara Az Zahra; Redi Hermanto; Dedi Nurjamil (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Junior high school students' mathematical reasoning ability still needs improvement, particularly in presenting mathematical information, formulating conjectures, applying concepts logically, evaluating the validity of arguments, and drawing conclusions. Therefore, this study aimed to develop a Realistic Mathematics Education (RME)-based Student Worksheet (SW) on statistics for eighth-grade junior high school students that is valid, practical, and limitedly effective in facilitating students' mathematical reasoning ability. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research participants included two material experts, two media experts, 10 students in a small-group trial, and 25 eighth-grade students of SMP Negeri 13 Tasikmalaya in a field trial. Data were collected through interviews, validation sheets, student response questionnaires, and mathematical reasoning ability tests. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the developed worksheet achieved a validity score of 88% from material experts and 95% from media experts, both categorized as highly valid. The practicality test indicated a student response rate of 91.5%, categorized as highly practical. The product's effectiveness was evaluated on a limited basis through a mathematical reasoning ability test, which showed a classical mastery level of 80%. These findings indicate that the RME-based Student Worksheet can facilitate students' mathematical reasoning ability in learning statistics. Therefore, the developed worksheet is feasible to be used as an alternative teaching material that supports contextual and student-centered mathematics learning.